Banking-on-the-Average Rules. (29th January 2019) - Gersbach, Hans; Hahn, Volker
Abstract: In this article, we introduce a new way to determine requirements for bank capital: banking-on-the-average rules. Under these rules, a bank's required level of equity capital is monotonically increasing in the realized equity capital of its peers. In a simple model, we illustrate the workings of banking-on-the-average rules. We show that in booms, these rules can prevent banks from taking excessive risks. Moreover, they alleviate the socially harmful procyclicality of conventional equity-capital rules, which may induce banks to cut back excessively on lending. Finally, we argue that under these rules, prudent banks can impose prudence on other banks. In addition, banking-on-the-average rules ensure the build-up of bank equity capital in booms and thus avoid excessive leverage. (JEL codes: G21, G28)